Heparan Sulfates Support Pyramidal Cell Excitability, Synaptic Plasticity, and Context Discrimination - Minge, Daniel (Cereb Cortex, 2017)
Heparan sulfate (HS) proteoglycans represent a major component of the extracellular matrix and are critical for brain development. However, their function in the mature brain remains to be characterized. Here, acute enzymatic digestion of HS side chains was used to uncover how HSs support hippocampal function in vitro and in vivo. We found that long-term potentiation (LTP) of synaptic transmission at CA3–CA1 Schaffer collateral synapses was impaired after removal of highly sulfated HSs with heparinase 1. This reduction was associated with decreased Ca(2+) influx during LTP induction, which was the consequence of a reduced excitability of CA1 pyramidal neurons. At the subcellular level, heparinase treatment resulted in reorganization of the distal axon initial segment, as detected by a reduction in ankyrin G expression. In vivo, digestion of HSs impaired context discrimination in a fear conditioning paradigm and oscillatory network activity in the low theta band after fear conditioning. Thus, HSs maintain neuronal excitability and, as a consequence, support synaptic plasticity and learning.